Studi literatur: Optimalisasi Model Discovery Learning dalam Peningkatan Pemahaman Konsep, Sikap Ilmiah, Berpikir Kritis, dan Hasil Kognitif Siswa pada Materi Fisika: Penelitian - Ulil Hidayah; Meliati; Zukhrufi Nahla; Mariati Purnama Simanjuntak (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the optimization of the Discovery Learning model in improving conceptual understanding, scientific attitudes, critical thinking, and students’ cognitive outcomes in physics learning through a literature review. The research method used is a narrative review with a descriptive analysis technique that collects various information from references related to the implementation of discovery learning in physics material. Data were obtained from accredited national and international journals by considering methodological quality and topic relevance. The data collection technique was carried out through scientific article searches, data filtering, and secondary document analysis. The analysis results show that the implementation of the Discovery Learning model can be an effective alternative learning approach, as it has been proven to enhance students’ conceptual understanding of physics, scientific attitudes, and critical thinking. In addition, Discovery Learning also contributes to improving students’ cognitive outcomes through more active, interactive, and meaningful learning activities.